Поиск in silico у актиномицетов паттернов, гомологичных LndJ-белку Streptomyces globisporus 1912 - Полищук, Л.В.; Лукьянчук, В.В. (Фактори експериментальної еволюції організмів, 2013)
The aim – to identify distribution of LndJ-like proteins among microorganisms and homology of their patterns. Method. Available Internet databases of information about primary structure of microbial DNAs and proteins on server NCBI were used. In silico analysis of Internet bases was done using available technical possibilities of program BLAST. The criterion for patterns selection was amino acid sequence of LndJ-protein of Streptomyces globisporus 1912. Results. Wide spreading of LndJ-homologous patterns among microorganisms of different taxonomic groups was detected, but the majority (97,6 %) is representatives of type Actinobacteria. The presence of LndJ-pattern orthologs with varying degree of homology (42 % to 95 %) was shown in 11 anguacyclines producing strains. Two of them each had two patterns for LndJ-paralogs (S. fradiae 2717 and Micromonospora sp. Tu6368). Strains S. antibioticus Tu6040 and S. globisporus 1912 each had (from 2 antiporters) only one ortholog of LndJ pattern. Conclusion. Antiporters with varying degrees of similarity to LndJ-protein are widespread among microorganisms as defense against their own antibiotics well as in ones that do not produce any biocides.